The Association Among Parental Bonding, Depression, Social Aggression, and Criminal Assault: Are There Gender Differences Between Male and Female Youth Offenders? - Tisak, John (Journal of interpersonal violence, 2021)
This research examined similarities and differences in gender regarding social aggression, criminal assault, depression, and familial factors. The participants were 251 youth offenders (158 males) who were arrested and incarcerated in a juvenile facility. The measures consisted of self-reported acts of social aggression, simple and aggravated assault, subtypes of depression, and self-reports on parental care and control. Our data demonstrate the importance of including gender, types of aggression/assault, subtypes of depression, and familial factors when examining their association. For example, less parental care predicted more social aggression for both males and females. However, neither did parental care predict aggravated assault for either gender, nor did parental care predict general depression or anhedonia. Parental control had different impact depending on gender. More parental control increased rates of social aggression and simple assault for females but not for males. Symptoms of general depression predicted committing simple assault for both males and females, but not anhedonia. However, general depressive symptoms and anhedonia were associated with committing aggravated assault for both genders. Policy implications were discussed.